Answer:
Writing the given equation in slope-intercept form we have;
![\begin{gathered} y=(x)/(5)-(3)/(25) \\ or \\ y=(1)/(5)x-(3)/(25) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qrcf8fhhthdiganjecbfa3dwd2bckv9ygd.png)
Step-by-step explanation:
Given the linear equation;
![5x-25y=3](https://img.qammunity.org/2023/formulas/mathematics/college/bym1n29m3dl0cc5csk8650l9069mfw7so5.png)
We want to turn the given linear equation to slope-intercept form.
![\begin{gathered} y=mx+b \\ m=\text{slope} \\ b=y-\text{intercept} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g4ctnygvscceci91ss8fflha4rkq3ay86g.png)
To do that, let us make y the subject of formula;
subtract 5x from both sides;
![\begin{gathered} 5x-5x-25y=-5x+3 \\ -25y=-5x+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/63zo28posf34ebm8ftcy7wf3utanzg72p5.png)
divide both sides by -25 (the coefficient of y);
![\begin{gathered} (-25y)/(-25)=(-5x)/(-25)+(3)/(-25) \\ y=(x)/(5)-(3)/(25) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wbpxun36gh7vq1o5fntvqimd0nceybk3lr.png)
Therefore, writing the given equation in slope-intercept form we have;
![y=(x)/(5)-(3)/(25)](https://img.qammunity.org/2023/formulas/mathematics/college/pn1plz2nt3w7t2kblzagzociwlj5cta9ma.png)